The effects of self-regulated learning intervention on students’ motivation in learning history - May Lee, Yong (2013)
In academic and educational field, self-regulated learning (SRL) has drawn great interest for educational research in the past few decades because of its characteristics that could influence students learning behavior and their achievement levels. Previous studies have revealed the importance of SRL by linking it to positive motivation, application of appropriate learning strategies and desirable academic outcomes. SRL studies in Malaysia mainly focus on the examination of factors and predictors that affect students SRL. No research was conducted to determine the effectiveness of SRL strategies intervene students motivation and use of learning strategies in learning. As such, the main purpose of this study is to investigate student motivational level and use of learning strategies in learning History before and after intervention program. In order to attain comprehensive picture and rich information for teachers and policy makers to design appropriate learning contexts in schools, SRL strategies used in this study has been integrated into form four History. This is a pre- and post-test quasi-experimental design which consists of 58 form four students from a secondary school. Thirty (30) of them were in experimental group and twenty eight (28) were in control groups. Sequential quantitative and qualitative data collections were engaged. Motivated Strategies for Learning Questionnaire (MSLQ) was used as research instrument to collect quantitative data in this study whereas Self-regulated learning Interview Schedule (SRLIS) was used as qualitative research instrument. T-test was used as statistical method to analyze quantitative data and thematic transcription was used to analyze qualitative data. Statistic findings indicate that mean score of student motivation and use of learning strategies increased significantly after intervention of SRL strategies.